A history of Christian doctrine ; v. 1 - Shedd, William Greenough Thayer, 1820-1894 (Mineapolis, MN Klock and Klock, 1978)
Contents : v. 1 : Introduction ; bk 1 : Influence of philosophical systems upon the construction of Christian doctrine ; bk 2 : History of Apologies ; bk 3 : History of theology (Trinitarianism) and Christology. Includes bibliographical references.
Originally published 1889, Charles Scribner's sons.
Keywords: Doctrine (theology) -- history